Impact of DNA methylation of the human mesoderm-specific transcript (MEST) on male infertility - Tayebeh Amjadian; Parichehreh Yaghmaei; Hayati Roodbari Nasim; Kheirollah Yari (Heliyon, 2023)
Male infertility accounts for nearly 40%–50% of all infertile cases. One of the most prevalent disorders detected in infertile men is errors in the MEST differentially methylated region (DMR), which has been correlated with poor sperm indexes. The aim of our study was to characterize the methylation pattern of the MEST gene, along with assessing seminal factors and chromatin condensation in sperm samples from both infertile patients and fertile cases, all of whom were candidates for intracytoplasmic sperm injection. We collected forty-five semen specimens from men undergoing routine spermiogram analysis at the Infertility Treatment Center. The specimens consisted of 15 samples of normospermia as the control group, 15 individuals of asthenospermia, and 15 individuals of oligoasthenoteratospermia as the cases group. Standard semen analysis and the chromatin quality and sperm maturity tests using aniline blue staining were performed. The DNA from spermatozoa was extracted and treated with a sodium bisulfite–based procedure. The methylation measure was done quantitatively at the DMRs of the MEST gene by quantitative methylation-specific polymerase chain reaction (qMSP). The mean percentages of total motility, progression, and morphology in normospermia were significantly higher than oligoasthenoteratospermia and asthenospermia, and they were substantially higher in asthenospermia compared to oligoasthenoteratospermia (P ≤ 0.05). The mean percentages of histone transition abnormality and MEST methylation in oligoasthenoteratospermia were significantly higher than asthenospermia and normospermia (P ≤ 0.05). A negative correlation existed between the histone transition abnormality and MEST methylation with sperm parameters. In conclusion, chromatin integrity, sperm maturity, and MEST methylation may be considered important predictors for addressing male factor infertility. Therefore, we suggest that male infertility may be linked to methylation of the imprinted genes.